Evaluation of primary high-grade osteosarcoma by surgical resection in PT Birta city hospital - Belbase, Rupesh Jung; Rayamajhi, Asmita; Lamichhane, Ritu; Basnet, Anil Kimar; Limbu, Kumud Kumar; Nepali, Dikshya (International Journal of Research in Orthopaedics, 2024)
Background: Classic OS had a 20% five-year survival rate during most of the 20th century. Adjuvant chemotherapy was first used to treat OS in the 1970s, raising survival rates to 50%. The standard course of treatment for OS includes surgery, neoadjuvant chemotherapy, and adjuvant chemotherapy. When treating a patient with soft tissue and bone sarcomas, the extent of surgical procedures is frequently described using surgical oncologic classifications. Radical resection refers to the removal of the whole bone or compartment harboring the tumor, whereas wide resection refers to the removal of the affected area of the bones with a cuff of healthy tissue. Methods: The study conducted a retrospective analysis of 120 patients who visited to orthopedic outpatient department of PT Birta city hospital and research center, Nepal from October 2019 to November 2022. Radical resection was defined as the removal of the entire affected bone, while wide resection was described as partial bone excision. The baseline characteristics of the patients were analyzed and the data regarding radical and wide resection in osteosarcoma (OS) was evaluated. Results: The analyzed report shows that 65/120 (54.1%) radical resections and 55/120 (45.8%) wide excisions were the extent of the resection. On the other hand, a central review of the extent of resection data revealed 100/120 (83.3%) wide excisions and 20/120 (16.6%) radical resections. Conclusions: OS is currently treated with extensive resection, neoadjuvant chemotherapy, and adjuvant chemotherapy, with a strict emphasis on the overall intensity of treatment and prompt restart of post-resection chemotherapy.